IEEE MTT-S International Microwave Symposium Digest, 2005. 2005
DOI: 10.1109/mwsym.2005.1516547
|View full text |Cite
|
Sign up to set email alerts
|

“Distortion-Free” Varactor Diode Topologies for RF Adaptivity

Abstract: Varactor diode-based circuit topologies, which can act as high-Q "distortion-free" tunable capacitive elements, are presented. These diodes are implemented in a novel ultra low-loss silicon-on-glass technology, with resulting measured Q's of over 200 at 2 GHz. The measured IM3 improvement compared to traditional single varactor tuning techniques is greater than 30 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 6 publications
2
55
0
Order By: Relevance
“…However, improved varactor diode-based circuit topologies, along with a high performance varactor diode process technology, have recently been demonstrated with very low distortion [17]. In addition, a silicon-based process technology was demonstrated with diodes Q's ranging from 100 to over 500 at 2 GHz, with capacitance values up to 50 pF, and with extremely low parasitic capacitances [18]. These developments revive interest in varactor diodes as a viable tuning approach for high-performance SDR frontends.…”
Section: High-quality Tunable Rf Varactor Diodes For Software Definedmentioning
confidence: 99%
“…However, improved varactor diode-based circuit topologies, along with a high performance varactor diode process technology, have recently been demonstrated with very low distortion [17]. In addition, a silicon-based process technology was demonstrated with diodes Q's ranging from 100 to over 500 at 2 GHz, with capacitance values up to 50 pF, and with extremely low parasitic capacitances [18]. These developments revive interest in varactor diodes as a viable tuning approach for high-performance SDR frontends.…”
Section: High-quality Tunable Rf Varactor Diodes For Software Definedmentioning
confidence: 99%
“…Antiparallel and back-to-back circuit topologies were introduced and experimentally verified for achieving minimum distortions [7]. Since then, several research groups have demonstrated the effectiveness of implementing this idea in BST, MEMS and varactor diode technologies to enhance linearity of the devices [8][9][10][11]. A linearity improvement technique based on BST-stacked parallel-plate capacitors has been analysed by connecting several capacitors in series, which reduced the RF swing across each capacitor [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…3), which form a so-called varactor stack (VS). A high ohmic resistor and two diodes in anti-parallel configuration have been used to realize sufficiently high impedance for the VS center tap, in order to avoid linearity degradation for narrow tone spacings [7]. Each VS is independently controlled through its center-tap voltage to achieve the desired capacitance variation and impedance transformation.…”
Section: Optimum Loading Conditonsmentioning
confidence: 99%
“…2) are implemented using the TU Delft siliconon-glass technology, which has been customized for the implementation of ultra low-loss high performance varactors (Q>100@2GHz). By using these varactors in an anti-series configuration, a tunable capacitor with extremely low distortion is realized [7]. The inductors were implemented using bond-wires to facilitate some additional adjustment of the inductances values as well.…”
Section: Optimum Loading Conditonsmentioning
confidence: 99%
See 1 more Smart Citation